Gambling decisions : the influence of difficulty, stakes and self-determination. - Sim, Carol Wei Shi. (2009)
This study examines the relationships between gambling factors like difficulty level and stakes, with gambling decisions. It also looked at the influence of self-determination on these relationships. Six hypotheses were tested on an undergraduate sample and a public sample, investigating if similar patterns were present. Results showed mixed support for the influence of self-determination on the relationships, with stronger support found for its influence on stakes and gambling decisions in the student sample. The negative relationship between gambling frequency, difficulty and loss amount was also supported. However, no support was found for the predicted positive relationship between gambling frequency and payout amount. These findings provided new insights about gambling behaviors suggesting a possible influence of an individual’s self-determination on gambling motivation.